2012
DOI: 10.1039/c2cc36651g
|View full text |Cite
|
Sign up to set email alerts
|

Solution mediated phase transformation (RHO to SOD) in porous Co-imidazolate based zeolitic frameworks with high water stability

Abstract: Here we report a highly porous, water stable Co based ZIF [CoNIm (RHO)] and its solution mediated phase transformation to a less porous and water unstable ZIF [CoNIm (SOD)]. CoNIm (RHO) has high Langmuir surface area [2087 m(2) g(-1)] as well as high water adsorption [200 cm(3) (STP) g(-1)] capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 15 publications
6
66
0
Order By: Relevance
“…The materials were synthesised according to methods reported in the literature [22][23][24][25][26][27][28][29].…”
Section: Methodsmentioning
confidence: 99%
“…The materials were synthesised according to methods reported in the literature [22][23][24][25][26][27][28][29].…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for the SOD phase in the M3 diffraction pattern include the intense reflection at 7.31°, as well as at 10.24°, and 12.65°, which overlay with the simulated SOD phase (ZIF-8) [33]. The RHO phase is evident from reflections at 4.30°, 6.08°, 7.45°, 8.60°, and 9.63°that overlay with the RHO topology seen for ZIFs [36]. The ratio of SOD to RHO was calculated to be 1:2.…”
Section: Sim-1 (Sod Rho) Fabrication Using Ex Situ Methods (M3)mentioning
confidence: 93%
“…The larger crystals had an average size of 370 ± 8.6 nm and the smaller crystals were *100 nm. Previously a SOD and RHO mixture was described for ZIF, CoNIm, and it was reported that RHO transforms into SOD over time [36]. However, the M3 synthesis does not seem to be affected by time, since after 48 h the SOD/RHO ratio did not change.…”
Section: Sim-1 (Sod Rho) Fabrication Using Ex Situ Methods (M3)mentioning
confidence: 95%
See 2 more Smart Citations